2012
DOI: 10.11646/zootaxa.3227.1.3
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Glyptapanteles (Hymenoptera: Braconidae: Microgastrinae), a larval parasitoid of Elymnias hypermnestra (Linnaeus) (Lepidoptera: Nymphalidae), along with some new host records of parasitoids from Peninsular India

Abstract: A new species, Glyptapanteles hypermnestrae Gupta and Pereira, is described from Maharashtra, India, and comparedwith closely allied species. This new species was bred from parasitized larvae of Elymnias hypermnestra (Linnaeus) (Lep-idoptera: Nymphalidae). In addition to this, two hymenopteran parasitoids, Apanteles folia Nixon (Braconidae: Microgas-trinae) and Brachymeria indica (Krausse) (Chalcididae), are for first time reported parasitizing larvae of Arhopalaamantes (Hewitson) (Lepidoptera: Lycaenidae) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Apanteles papilions endoparasite recovered from the larvae of the LBF same findings of (Resham et al, 1986) reported Apanteles lunatus and Pteromalus puparum parasites reported from the larvae of LBF. (Gupta and Pereira, 2012) documented Glyptapanteles hypermnestrae parasitiod wasps found the larvae of Elymnias hypermenestra, also A. folia and B. indica first time from the pupae and larvae of the Arhopala amantes butterfly. Another species of endoparasite LBF larvae Distatrix papilionis found with the comparable work of Bhoje and Charaple, (2020) reported the first time A. papiliones form the larvae of the lemon butterfly in Maharashtra, India.…”
Section: Discussionmentioning
confidence: 99%
“…Apanteles papilions endoparasite recovered from the larvae of the LBF same findings of (Resham et al, 1986) reported Apanteles lunatus and Pteromalus puparum parasites reported from the larvae of LBF. (Gupta and Pereira, 2012) documented Glyptapanteles hypermnestrae parasitiod wasps found the larvae of Elymnias hypermenestra, also A. folia and B. indica first time from the pupae and larvae of the Arhopala amantes butterfly. Another species of endoparasite LBF larvae Distatrix papilionis found with the comparable work of Bhoje and Charaple, (2020) reported the first time A. papiliones form the larvae of the lemon butterfly in Maharashtra, India.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, types from the Natural History Museum, London, UK (BMNH) housing collections of Glyptapanteles from South East Asia were examined. Identification was undertaken consulting Wilkinson 1928 [ 10 ], Nixon 1965 [ 11 ], Mason 1981 [ 3 ], Gupta & Pereira 2012 [ 12 ], Gupta 2013 [ 13 ], Gupta & Fernández-Triana 2014 [ 14 ] and Yu et al 2012 [ 15 ] was consulted for host associations. Most of the images of host caterpillar/cocoons were taken with either Nikon D7000 with Nikkor 105mm macro lens or Sony DSLR-A100 Digital SLR Camera with Tamron 90mm macro lens.…”
Section: Methodsmentioning
confidence: 99%